Epidemiology of wheeze among preschool children: a population-based cross-sectional study from rural Sri Lanka. Issue 7 (7th July 2021) - Rajapakse Mudiyanselage, Shashanka Indeevara Rajapakse; Amarasiri, Wadu Arachchige Dharshika Lakmali; Yasaratne, Bannek Mudiyanselage Gedara Duminda; Warnasekara, Janith; Agampodi, Suneth
Abstract : Objectives: To assess the prevalence of wheeze and factors associated with its severity among 3–6 years old children. Methodology: Design: A population-based, cross-sectional study using the WHO 30 cluster methodology with probability proportionate to size sampling. Setting: 36 preschools registered at the divisional secretariat offices of Anuradhapura district, Sri Lanka. Participants: We recruited 1060 preschool children from 36 preschools aged 3–6 years. Main outcome measurements: We used the International Study of Asthma and Allergy in Childhood questionnaire to assess the prevalence, symptomatology and associated factors of wheeze. Results: The study sample consisted of 548 (51.70%) male and 512 (48.30%) female children with a mean age of 4.41 (±0.66) years. At least one wheezing episode ever was reported in 323 (30.47%; 95% CI 27.71% to 33.34%) children and 247 (23.30%; 95% CI 20.79% to 25.97%) children had a wheezing attack in the preceding year. Severe episodes of wheezing were reported in 76 (7.17%; 95% CI 5.69% to 8.89%) participants. However, only 27 (35.53%; 95% CI 24.88% to 47.34%) children with severe wheezing had been diagnosed as asthmatics by a clinician. The identified independent risk factors for severe wheeze were allergic rhinitis (OR 6.90; 95% CI 3.84 to 12.40), domestic dog(s) (OR 2.34; 95% CI 1.01 to 5.40), frequent consumption of skipjack tuna (OR 1.94; 95% CI 1.11 to 3.39) and passive smoking (OR 1.70; 95% CI 0.93 to 3.11) while living in a house with a cement floor is a protective factor (OR 0.41; 95% CI 0.21 to 0.80). Conclusion: Wheezing commonly affects one-fourth of preschool children in rural Sri Lanka. Severe wheezing is often not diagnosed as asthma despite frequent symptoms, probably due to hesitancy in labelling preschool children as asthmatics. Allergic rhinitis, domestic dogs, frequent consumption of Skipjack tuna fish and exposure to passive smoking were independent risk factors for severe wheeze.